2019
DOI: 10.1016/j.stemcr.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

H3K18ac Primes Mesendodermal Differentiation upon Nodal Signaling

Abstract: SummaryCellular responses to transforming growth factor β (TGF-β) depend on cell context. Here, we explored how TGF-β/nodal signaling crosstalks with the epigenome to promote mesendodermal differentiation. We find that expression of a group of mesendodermal genes depends on both TRIM33 and nodal signaling in embryoid bodies (EBs) but not in embryonic stem cells (ESCs). Only in EBs, TRIM33 binds these genes in the presence of expanded H3K18ac marks. Furthermore, the H3K18ac landscape at mesendodermal genes prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…1f, g ). We also found that TRIM33— a Nodal signaling-specific chromatin reader that associates with H3K9me3 and H3K18ac dual marks to regulate the expression of mesendoderm LDTFs 21 , 25 —is essential for Gm11549 induction during mesendoderm differentiation and Gm11549 transcription was not induced by Nodal/Activin stimulation in Trim33 null cells (Fig. 1g , and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…1f, g ). We also found that TRIM33— a Nodal signaling-specific chromatin reader that associates with H3K9me3 and H3K18ac dual marks to regulate the expression of mesendoderm LDTFs 21 , 25 —is essential for Gm11549 induction during mesendoderm differentiation and Gm11549 transcription was not induced by Nodal/Activin stimulation in Trim33 null cells (Fig. 1g , and Supplementary Fig.…”
Section: Resultsmentioning
confidence: 65%
“…We analyzed the ChIP-seq data (TRIM33, SMAD2/3, SMAD4, FOXH1) as previously described 21 , 44 . Briefly, the data were trimmed using TrimGalore (version 0.6.1) and then aligned to mm10 using Bowtie2 (version 2.3.3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AP2-G2 is associated with H3K18ac and H3K23ac and interacts with ISWI, which has a relatively high homology to TRIM24 (42% identity), which is a reader of H3K18ac and H3K23ac ( 106 , 107 ). Furthermore, the writers of H3K18ac and H3K23ac, p300/CBP activator ( 108 , 109 , 110 ), have homology to the P. falciparum histone acetyltransferase, GCN5 (PF3D7_0823300, 34% identity). Furthermore, TRIM24 has been described as CBP-associated proteins ( 111 ).…”
Section: Resultsmentioning
confidence: 99%
“…AP2-G2 additionally interacts with other chromatin regulation proteins, including a chromatin assembly factor 1 subunit A (PF3D7_0501800, CAF1A) and a ISWI chromatin-remodelling complex ATPase (PF3D7_0624600, ISWI), which interacts with a Snf2-related CBP activator (PF3D7_0820000). Both ISWI and Snf2/CBP are homologues of the mammalian H3K18acK23ac writer and reader, p300 and TRIM24, respectively (Halasa et al ., 2019; Luo et al ., 2019; Lv et al ., 2017; Ma et al ., 2016; Tsai et al ., 2010). This suggest that the SAGA-like complex of P. falciparum has as core GCN5/ADA2/PHD2 but in gametocytes, association with the H3K18acK23ac combination includes the additional ISWI/SNF complex effectors.…”
Section: Resultsmentioning
confidence: 99%